Pengaruh Kemampuan Kerja, Disiplin Kerja Dan Konflik Kerja Terhadap Prestasi Kerja Guru Madrasah Ibtidaiyah Negeri 6 Kota Banda Aceh - Cut Ainun Jariah; T Lukman Ibrahim; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The aim of this research is to determine the magnitude of the influence of work ability, work discipline and work conflict on the work performance of teachers at Madrasah Ibtidaiyah Negeri 6 Banda Aceh City. This research uses a quantitative approach using primary data through questionnaires. Based on the results of the t test (partial) regarding the work ability variable, the value tcount>ttable (1.708>1.677), with a significant value of 0.004 <0.05, then Ha is accepted. This means that work ability influences the work performance of employees at Madrasah Ibtidaiyah Negeri 6 Banda Aceh City. The results of the t test (partial) regarding the work discipline variable value tcount>ttable (2.021>1.677), with a significant value of 0.002 <0.05, then Ha is accepted. This means that work discipline influences the work performance of employees at Madrasah Ibtidaiyah Negeri 6 Banda Aceh City. Furthermore, the results of the t test (partial) regarding the work conflict variable have a value of tcount>ttable (2.988>1.677), with a significant value of 0.004 <0.05, then Ha is accepted. This means that work conflict affects the work performance of employees at Madrasah Ibtidaiyah Negeri 6 Banda Aceh City. Based on the results of the simultaneous f test, work ability, work discipline and work conflict together have a significant influence on employee work performance at Madrasah Ibtidaiyah Negeri 6 Banda Aceh City. The f test results show that the calculated F value is greater than the F table and the significant value is below 0.05.